Analysis of Taurine Content in Microalgae Tetraselmis sp. Cultured at Different Salinities - Nurafiah, Eva; Widiastuti, Endang Linirin; Maharani, Henni Wijayanti (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2023)
Taurine is a non-essential sulfur-containing amino acid with the chemical formula C2H7NO3S. These compounds play an important role in maintaining the smooth running of various processes in the body. Tetraselmis sp. is one of the microalgae known to have a taurine biosynthetic pathway via the serine/sulfate pathway. The purpose of this study was to determine the effect of culture salinity on taurine content produced by microalgae Tetraselmis sp. which was dissolved using 96% ethanol. The samples obtained were then tested using UV-Vis spectrophotometry using standard synthetic taurine as a comparison. Based on the research results, the maximum absorption was obtained at a wavelength of 630 nm, and the regression equation y = 0.001x + 0.033 was obtained and had a correlation coefficient of r = 1. Based on the analysis results showed that all samples contained taurine. Samples at a salinity of 25 ppt contained an average of 2.82 ml/100g of taurine, while a culture salinity of 35 ppt contained an average of 4.03 ml/100g of taurine. From these data it is known that the highest taurine level was found at a culture salinity of 35 ppt, while the lowest taurine level was at a culture salinity of 25 ppt. This indicates that the higher the culture salinity, the higher the taurine content produced by the microalgae Tetraselmis sp. The phenomenon of increased taurine due to salinity stress is thought to be due to an increase in free amino acids in microalgae cells to produce metabolites that are used to defend themselves due to salinity stress. The function of taurine in this microalgae is thought to be an organic osmolyte in the cells of the Tetraselmis sp. microalgae.